Labor Migration, EU Enlargement, and the Great Recession - Kahanec, Martin; Zimmermann, Klaus F.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg(Imprint), 2016)
This volume extends and deepens our knowledge about cross-border mobility and its role in an enlarged EU. More specifically, its main purpose is to enlighten the growing and yet rather uninformed debate about the role of post-enlargement migration for economic adjustment in the crisis-stricken labor markets of the Eurozone and the EU as a whole. The book addresses the political economy aspects of post-enlargement migration, including its broader political contexts, redistributive impacts, but also nationalization of the enlargement agenda. It also covers the experience of receiving and sending countries with post-enlargement migration and its role during the current crisis. Renowned experts in the field study, whether and how post-enlargement mobility has enabled the EU to absorb asymmetric economic shocks, how it has affected the European welfare systems, and whether it has contributed to the sustainability of the Eurozone. The authors also evaluate brain circulation as a sought-after vehicle of improved allocative efficiency of EU labor markets and propose a policy agenda for mobility in an enlarged EU.
The Free Movement of Workers in an Enlarged European Union: Institutional Underpinnings of Economic Adjustment -- The Redistributive Impacts of Migration after the EU's Eastern Enlargement -- Migration in Italy is Backing the Old Age Welfare -- Migration 10 Years After: EU Enlargement, Closed Borders, and Migration to Germany -- Ireland's Recession and the Immigrant-native Earnings Gap -- Post-enlargement Migration and Adjustment in a Receiving Country: The Case of Sweden -- Labor Mobility as an Adjustment Mechanism in the UK during the Great Recession -- Migration, Crisis and Adjustment in an Enlarged EU: The Spanish Perspective -- Did Post-enlargement Labor Mobility Help the EU to Adjust during the Great Recession? The Case of Slovakia -- Migration as an Asset? Polish Returnees at the Time of the Crisis -- Should I Stay or Should I Go? Romanian Migrants during Transition and Enlargements -- The Experiences of a New Emigrant Country: Emerging Migration from Hungary -- Migration Experience of the Baltic Countries in the Context of Economic Crisis -- Labor Market Transitions during the Great Recession in Estonia -- Labor Market Policies and Labor Market Flexibility during the Great Recession: The Case of Estonia -- Returning Home at Times of Trouble? Return Migration of EU Enlargement Migrants during the Crisis -- EU Post-Enlargement Migration and the Great Recession: Lessons and Policy Implications.
Keywords: Labor economics; Migration; European Economic Community lite; International Economics; Economic policy; Population Economics; European Integration